FORMULASI INDIKATOR DAN TARGET ANGKA PENJARINGAN SUSPEKTB BTA+ UNTUK PUSKESMAS DI KABUPATEN JEMBER - Ariyanto, Yunus; Ramani, Andrei (IKESMA, 2012)
Even though for two last years the national target of rate of cases that succeed to be found from suspects; that represented as Case Detection Rate (CDR) has been fulfilled, performances of each forty-nine Community Health Center in Jember, Indonesia was fluctuated. Two primary factors, that contributing to CDR are Error Rate and Suspect Rate. Suspect rate never been evaluated by TB+ program. This research was aimed to produce Suspect Rate indicator and target, that applicable for Community Health Center in Jember.This study was a part of Research and Development (R&D), towards to four years data of forty-nine Community Health Center in Jember.From this study concluded that applicable Suspect Rate indicator definites as âAmount of checked suspects (its phlegm) among 10.000 residents at one particular Community Health Center region in one yearâ and the target that realistic is minimum 75 checked suspects among 10.000 residents.